Elicited imitation as a measure of second language proficiency: A narrative review and meta-analysis. (October 2016) - Yan, Xun; Maeda, Yukiko; Lv, Jing; Ginther, April
Elicited imitation (EI) has been widely used to examine second language (L2) proficiency and development and was an especially popular method in the 1970s and early 1980s. However, as the field embraced more communicative approaches to both instruction and assessment, the use of EI diminished, and the construct-related validity of EI scores as a representation of language proficiency was called into question. Current uses of EI, while not discounting the importance of communicative activities and assessments, tend to focus on the importance of processing and automaticity. This study presents a systematic review of EI in an effort to clarify the construct and usefulness of EI tasks in L2 research. The review underwent two phases: a narrative review and a meta-analysis. We surveyed 76 theoretical and empirical studies from 1970 to 2014, to investigate the use of EI in particular with respect to the research/assessment context and task features. The results of the narrative review provided a theoretical basis for the meta-analysis. The meta-analysis utilized 24 independent effect sizes based on 1089 participants obtained from 21 studies. To investigate evidence of construct-related validity for EI, we examined the following: (1) the ability of EI scores to distinguish speakers across proficiency levels; (2) correlations between scores on EI and other measures of language proficiency; and (3) key task features that moderate the sensitivity of EI. Results of the review demonstrate that EI tasks vary greatly in terms of task features; however, EI tasks in general have a strong ability to discriminate between speakers across proficiency levels (Hedges' g = 1.34). Additionally, construct, sentence length, and scoring method were identified as moderators for the sensitivity of EI. Findings of this study provide supportive construct-related validity evidence for EI as a measure of L2 proficiency and inform appropriate EI task development and administration in L2 research and assessment.